Hypoxia-adaptive pathways: a pharmacological target in fibrotic disease? - Strowitzki, Moritz; Ritter, Alina; Schneider, Martin (Pharmacological research, 2019)
Wound healing responses are physiological reactions to injuries and share common characteristics and phases independently of the injured organ or tissue. A major hallmark of wound healing responses is the formation of extra-cellular matrix (ECM), mainly consisting of collagen fibers, to restore the initial organ architecture and function. Overshooting wound healing responses result in unphysiological accumulation of ECM and collagen deposition, a process called fibrosis. Importantly, hypoxia (oxygen demand exceeds supply) plays a significant role during wound healing responses and fibrotic diseases. Under hypoxic conditions, cells activate a gene program, including the stabilization of hypoxia-inducible factors (HIFs), which induces the expression of HIF target genes counteracting hypoxia. In contrast, in normoxia, so-called HIF-prolyl hydroxylases (PHDs) oxygen-dependently hydroxylate HIF-α, which marks it for proteasomal degradation. Importantly, PHDs can be pharmacologically inhibited (PHI) by so-called PHD inhibitors. There is mounting evidence that the HIF-pathway is continuously up-regulated during the development of tissue fibrosis, and that pharmacological (HIFI) or genetic inhibition of HIF can prevent organ fibrosis. By contrast, initial (short-term) activation of the HIF pathway via PHI during wound healing seems to be beneficial in several models of inflammation or acute organ injury. Thus, timing and duration of PHI and HIFI treatment seem to be crucial. In this review, we will highlight the role of hypoxia-adaptive pathways during wound healing responses and development of fibrotic disease. Moreover, we will discuss whether PHI and HIFI might be a promising treatment option in fibrotic disease, and consider putative pitfalls that might result from this approach.
Gesehen am 30.10.2019